Cardiovascular function in 8- to 9-year-old singletons born after ART with frozen and fresh embryo transfer. Issue 3 (7th January 2022) - Mizrak, I; Asserhøj, L L; Lund, M A V; Kielstrup, L R; Greisen, G; Clausen, T D; Main, K M; Jensen, R B; Vejlstrup, N G; Madsen, P L; Pinborg, A
Abstract: STUDY QUESTION: Do 8- to 9-year-old singletons conceived after frozen embryo transfer (FET) or fresh embryo transfer (Fresh-ET) have increased arterial stiffness compared to naturally conceived (NC) children? SUMMARY ANSWER: The process of FET or Fresh-ET is not associated with altered cardiovascular function in 8- to 9-year-old singletons, including arterial stiffness, as compared to NC children. WHAT IS KNOWN ALREADY: ART has been suggested to influence cardiovascular risk factors (i.e. endothelial dysfunction, increased arterial blood pressure and insulin resistance). It is not known if ART procedures alter arterial stiffness in singletons. STUDY DESIGN, SIZE, DURATION: A cohort study was carried out, including 8- to 9-year-old singletons conceived after FET, Fresh-ET and NC children (50 children in each group). This study was conducted between November 2018 and August 2020. PARTICIPANTS/MATERIALS, SETTING, METHODS: In total, 150 singletons were identified through the Danish IVF Registry and the Medical Birth Registry. They underwent cardiac magnetic resonance imaging (CMR) and anthropometric measurements. Parental data were collected using questionnaires. NC children were matched by sex and birth year with FET/Fresh-ET children. Exclusion criteria were congenital heart disease, maternal gestational diabetes or maternal diabetes mellitus. Our primary outcome was arterial stiffness, which is assessed from noninvasive arterial blood pressure and aortic ascendens distensibility. The secondary outcome was the pulse wave velocity of total aorta and exploratory outcomes were left ventricular ejection fraction, mean arterial pressure, cardiac output and total peripheral resistance. Measurements and analyses were performed blinded to the child group. MAIN RESULTS AND THE ROLE OF CHANCE: Aortic ascendens distensibility of children conceived after FET and Fresh-ET did not differ from NC children (mean (SD): FET 11.1 (3.6) 10 −3 mmHg −1, Fresh-ET 11.8 (3.0) 10 −3 mmHg −1, NC 11.4 (2.8) 10 −3 mmHg −1, P > 0.05). Multivariate linear regression was performed to adjust for potential confounders (i.e. child sex and age, maternal BMI at early pregnancy and maternal educational level). Data showed no statistically significant differences between study groups and aortic ascendens distensibility. However, the fully adjusted model showed a non-significant tendency of lowered aortic ascendens distensibility in children born after FET compared to Fresh-ET ( β estimate (95% CI): −0.99 10 −3 mmHg −1 (−2.20; 0.21)) and NC children ( β estimate (95% CI): −0.77 10 −3 mmHg −1 (−1.98; 0.44)). Lastly, secondary and exploratory outcomes did not differ between the groups. Primary and secondary outcomes showed good intra-rater reliability. LIMITATIONS, REASONS FOR CAUTION: This study is possibly limited by potential selection bias as the participation rate was higher in the ART compared to the NC group. Also, in some variables, the study groups differed slightly from the non-participant population. The non-participant population (n = 1770) included those who were excluded, not invited to CMR scan, or declined to participate in this study. WIDER IMPLICATIONS OF THE FINDINGS: Our findings indicate that children born after FET or Fresh-ET do not have altered cardiovascular function, including arterial stiffness. This is reassuring for the future use of ART. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by the Novo Nordisk Foundation (grant reference number: NNF19OC0054340) and The Research Foundation of Rigshospitalet. All authors declared no conflict of interests. TRIAL REGISTRATION NUMBER: ClinicalTrials.gov identifier: NCT03719703.